Inventarisasi Tanaman Obat untuk Penderita Penyakit Tidak Menular di Kota Makassar - Asni Amin; Faradiba Faradiba (PHARMACY UMI JOURNAL SYSTEM, 2023)
Makassar City is one of the largest cities in the eastern region of Indonesia with the lifestyle of its society having undergone changes, starting from consuming instant food, lack of movement, and rarely exercising. So that, there is an increase in non-infectious diseases. People in the city of Makassar use traditional medicinal plants in accordance with the changing trend of people who return to nature